Comparison of pregnancy outcomes following fresh and electively frozen single blastocyst transfer in natural cycle and clomiphene-stimulated IVF cycles - Kato, K (Hum Reprod Open, 2018)
STUDY QUESTION: Are there any differences in live birth rates (LBR) following fresh blastocyst transfer in natural or clomiphene-stimulated cycles, or after elective blastocyst freezing in clomiphene-stimulated cycles followed by thawing and transfer at different time-points? SUMMARY ANSWER: Clomiphene citrate (CC) administration adversely affected the LBR after single fresh blastocyst transfer (SBT) in CC cycles compared with that in natural cycles, while this adverse effect of CC is not present when a single vitrified-warmed blastocyst transfer (SVBT) is performed in subsequent natural ovulatory cycles, regardless of the duration between CC administration and the day of SVBT. WHAT IS KNOWN ALREADY: CC affects uterine receptivity associated with a thinning of the uterine endometrium through an antioestrogenic effect. However, the duration that this adverse effect of CC on uterine endometrium persists after initial use is still unknown. STUDY DESIGN, SIZE, DURATION: A retrospective cohort study of 157 natural cycle IVFs followed by SBT and 1496 minimal ovarian stimulation with CC IVF cycles followed by SBT (n = 24) or SVBT (n = 1472) from January 2010 to December 2014 was conducted. SVBT cycles were classified into two groups according to the period between the last day of CC administration and the day of SVBT (A: ≤60 d and B: ≥61 d). All groups were then compared based on pregnancy outcomes (natural-SBT group: n = 157, CC-SBT group: n = 24, SVBT-A: n = 1143, SVBT-B: n = 329). PARTICIPANTS/MATERIALS, SETTING, METHODS: Women were aged 30–39 years at oocyte retrieval. In SVBT cycles, blastocysts were vitrified and warmed using a Cryotop safety kit. SVBT was performed in subsequent natural ovulatory cycles. The main outcomes were LBR and neonatal outcome, and both were compared among the groups. MAIN RESULTS AND THE ROLE OF CHANCE: The LBR in the CC-SBT group (29.2%, 7/24) was significantly lower compared with the natural-SBT (56.1%, 88/157) (P = 0.01) and SVBT-A (50.0%, 572/1143) (P = 0.04), but not SVBT-B (47.4%, 156/329), groups. Furthermore, multivariate logistic regression analysis revealed that the LBR was comparable among the natural-SBT and SVBT groups, but was significantly lower in the CC-SBT group (adjusted odds ratio: 0.324, 95% CI: 0.119–0.800, P = 0.01). No significant differences among all groups were observed for gestational age (P = 0.19), birthweight (P = 0.41) and incidence of malformation (P = 0.53). LIMITATIONS, REASONS FOR CAUTION: In this study we analysed a biased sample, based on clinical judgement regarding endometrial thickness, and the study was limited by its retrospective nature. The low statistical power caused by the group size disparity was also a limitation, especially in the CC-SBT group. Although the outcome showing inferiority of CC-SBT compared to natural-SBT is consistent with general findings in the literature, further large-scale clinical studies, ideally RCTs, are necessary to validate our results and clarify the prolonged effect of CC in SVBT cycles on pregnancy and neonatal outcomes. WIDER IMPLICATIONS OF THE FINDINGS: Our observation suggests that CC administered in minimal ovarian stimulation cycles affects adversely the pregnancy outcomes when SBT is performed. Therefore, for a CC-based minimal stimulation IVF cycle, we suggest that frozen embryo transfer should be performed in a subsequent natural ovulatory cycle to avoid the possibility of implantation failure associated with CC administration. STUDY FUNDING/COMPETING INTERESTS: The authors have no conflicts of interest to declare. No external funding was either sought or obtained.